2021
DOI: 10.3390/su13052788
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Funding and a Financially Viable Football Industry—Friends or Foes? A Norwegian Football League Perspective

Abstract: Financial distress has been frequently addressed in the sports business and management literature; however, surprisingly little attention has been devoted to implications for financial viability derived from funding beyond what the Union of European Football Association (UEFA) defines as relevant income in football, henceforth referred to as extraordinary funding. This study critically discusses and reflects upon whether extraordinary funding can contribute to financial viability. To address this issue, we dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Identifying the temporality of public aid is essential for measuring the effectiveness of sports policies put in place. In this respect, we agree with the conclusions of [19] for whom "it is useful to distinguish clearly between ex-ante and ex-post funding." For them, ex ante aid seems to be more effective in supporting and helping clubs to develop.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Identifying the temporality of public aid is essential for measuring the effectiveness of sports policies put in place. In this respect, we agree with the conclusions of [19] for whom "it is useful to distinguish clearly between ex-ante and ex-post funding." For them, ex ante aid seems to be more effective in supporting and helping clubs to develop.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Ref. [19] suggested that ex ante support is more relevant for providing effective support for clubs. For them, "ex-post funding can be argued to be counter-productive to financial viability (e.g., cloaking inadequate finances, providing incentives for overspending, and rewarding clubs that overspend), ex-ante funding is more in line with sound financial management (e.g., funds that are contingent upon a history of sound finances, incorporated in budgets).…”
Section: Public Financing Of Stadiums Has Characteristics Of the Five...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bennike et al (2020) consider professional football clubs in Denmark and state that the question of economic power remains top of the agenda because clubs are trying to balance financial stability with sporting success. Staying in Scandinavia, Jacobsen et al (2021) consider the case of Norwegian football and consider implications for financial viability derived from funding beyond what the Union of European Football Association (UEFA) defines as relevant income in football, referred to as extraordinary funding. They argue for regulatory bodies to take on a proactive role in promoting financial viability, primarily by providing incentives for decisions, such as those related to extraordinary funding, that are in line with sound financial management.…”
Section: Measuring Performance In Professional Team Sportsmentioning
confidence: 99%
“…In recent years, with the rapid development of China's economy, China's sports industry has also been greatly improved, the development speed is faster, but the overall scale is still not very large, in which there are still some problems [1][2][3]. Soccer industry is an important part of China's sports industry, soccer is a collective, backward project, is a popularity wide, high attention to the project, it is also designated by the State Council as one of the potential industries [4][5][6]. The soccer industry's development has reached the highest level in the country, as evidenced by this.…”
Section: Introductionmentioning
confidence: 99%